Service Quality and Income Tax Non-Compliance among Small and Medium Enterprises in Yemen - Ali Al-Ttaff, L. H.; Abdul-Jabbar, H. (Journal of Advanced Research in Business and Management Studies, 2020)
Almost all countries around the world are continuously facing problems and challenges with regards to compliance with tax rules and regulations. The scenario is prevalent in developing countries, especially the Middle East countries in general and Yemen in particular. Although many official reports in Yemen provided ample evidence of the existence of this problem in the country, there is, unfortunately, a lack of studies that provide causal explanations of this issue. This empirical study investigates the influence of tax service quality on taxpayer behaviour in the context of Yemeni small and medium enterprises (SME). Data have been collected from the Yemeni SMEs through a personally administered questionnaire. The analysis reveals that tax non-compliance in Yemen can be considered high among SME owner-managers. As part of a larger study of determinants of income tax compliance behaviour, this paper focuses on the perceived tax service quality factor. The tax service quality is perceived as low, indicating that the SME owner-manager seems to be not satisfied with the quality of services received from the tax authority. A simple regression analysis found that the perceived tax service quality has a significant negative influence on tax non-compliance behaviour. The study, therefore recommends that the tax authority of a country considers the relevant measures and strategies in improving the quality of tax services, which in turn enhances the level of tax compliance.